2023
DOI: 10.1364/oe.491792
|View full text |Cite
|
Sign up to set email alerts
|

Chromium oxide film for Q-switched and mode-locked pulse generation

Abstract: Chromium oxide (Cr2O3) is a promising material used in the applications such as photoelectrochemical devices, photocatalysis, magnetic random access memory, and gas sensors. But, its nonlinear optical characteristics and applications in ultrafast optics have not been studied yet. This study prepares a microfiber decorated with a Cr2O3 film via magnetron sputtering deposition and examines its nonlinear optical characteristics. The modulation depth and saturation intensity of this device are determined as 12.52%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Additionally, TMNs can exhibit plasmonic behavior in the visible and near-infrared range under certain conditions, such as variations in optical properties, chemical deposition, and structural size. 23,[96][97][98] For example, Sucheewa et al demonstrated that a hafnium nitride (HfN) thin film created through gas-timed RF magnetron sputtering exhibited an EF of 8.5 × 10 4 for MB molecules, which was largely attributed to an increased "hot spot" effect. The absorbance of the HfN thin film in the longer wavelength range (approximately 500-900 nm) is advantageous for surface plasmon resonance, which greatly enhances the electromagnetic mechanism on the surface.…”
Section: Sers Mechanism Of Inorganic Semiconductorsmentioning
confidence: 99%
“…Additionally, TMNs can exhibit plasmonic behavior in the visible and near-infrared range under certain conditions, such as variations in optical properties, chemical deposition, and structural size. 23,[96][97][98] For example, Sucheewa et al demonstrated that a hafnium nitride (HfN) thin film created through gas-timed RF magnetron sputtering exhibited an EF of 8.5 × 10 4 for MB molecules, which was largely attributed to an increased "hot spot" effect. The absorbance of the HfN thin film in the longer wavelength range (approximately 500-900 nm) is advantageous for surface plasmon resonance, which greatly enhances the electromagnetic mechanism on the surface.…”
Section: Sers Mechanism Of Inorganic Semiconductorsmentioning
confidence: 99%
“…Therefore, they have high temperature resistance like ceramic and have excellent electrical and thermal conductivity like metal. Compared to other materials [28][29][30] MAX phase exhibited low density, high modulus elasticity, good oxidation resistance and high melting point. These properties of MAX phase promote them as promising material to be used in high temperature applications.…”
Section: Introductionmentioning
confidence: 97%
“…35 Q-Switched and mode-locked pulses were generated from the erbium-doped fiber ring cavity with Cr 2 O 3 SA. 36 Dissipative solitons with a pulse width of 1.03 ps were generated as Nb x Re (1Àx) S 2 SA. 37 2D MXenes are early transition metal carbides and nitrides with a chemical formula of M n+1 X n T x (n = 1-3).…”
Section: Introductionmentioning
confidence: 99%